PENGARUH BUDAYA ORGANISASI TERHADAP MOTIVASI DENGAN LINGKUNGAN KERJA SEBAGAI MEDIATOR.: (Studi Kasus Pada Pegawai Kecamatan Tungkal Jaya) - Hendry Wijaya (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2022)
ABSTRACT : This study aims to explain how the influence of Organizational Culture on work motivation with the work environment as a mediating variable for the employees of the Tungkal Jaya District Office, Musi Banyuasin Regency, South Sumatra Province. The sample uses the Slovin formula. The data collection method used a questionnaire to the Tungkal Jaya Sub-District Head Office. The data were analyzed using the Quantitative Method with path analysis and partial hypothesis testing (Critical Ratio) using SPSS 20.0 software for windows and IBM AMOS 22. The results showed that the more effective path between the direct influence path is Organizational Culture on Work Motivation if compared to the indirect influence path, namely Organizational Culture on Work Motivation through the Work Environment, is a direct influence path, namely Organizational Culture on Work Motivation. The coefficient of determination (R2) for the influence of the Organizational Culture variable is able to explain the Work Environment Variable of 0.263 or 26.3%, while the remaining 73.7% is explained by other factors not examined. The influence of the Organizational Culture variable, through the Work Environment variable, is able to explain the Work Motivation Variable of 0.446 or 44.6%, while the remaining 55.4% is explained by other factors not examined.